2019
DOI: 10.1155/2019/1726964
|View full text |Cite
|
Sign up to set email alerts
|

Gateway to Recovery: A Comparative Analysis of Stroke Patients’ Experiences of Change and Learning in Norway and Denmark

Abstract: Objectives The recovery process is reported by stroke survivors to be a change process fraught with crises and hazard. Interaction with health professionals and others may play a central role in establishing renewed control over life. Research Questions (1) How do patients handle and overcome experienced changes after stroke? (2) How do they experience the support to handle these changes during the first year after stroke? (3) How do the similarities and differences transpire in Danish and Norwegian contexts? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…It seems that the activity was planned to suit the patient's individual needs. This finding was consistence with the suggestion made by [22], where it was suggested that the intervention activities should include a patient's self-management approach, involving meaningful activities and tailored to the individual patients. In these sessions, patients were observed to perform walking tasks using a walking stick or walking frame at the center part of C2 and using the route around the pergola, assisted by therapists at their side to support their balancing.…”
Section: Fig 5 Pattern Of Activities For Individual Sessionssupporting
confidence: 79%
See 3 more Smart Citations
“…It seems that the activity was planned to suit the patient's individual needs. This finding was consistence with the suggestion made by [22], where it was suggested that the intervention activities should include a patient's self-management approach, involving meaningful activities and tailored to the individual patients. In these sessions, patients were observed to perform walking tasks using a walking stick or walking frame at the center part of C2 and using the route around the pergola, assisted by therapists at their side to support their balancing.…”
Section: Fig 5 Pattern Of Activities For Individual Sessionssupporting
confidence: 79%
“…This activity was observed to encourage patients to communicate with peers and boost their confidence level. Group interventions that are well organized and structured played an important role to help patients to develop their cognitive and social abilities [22]. Meanwhile, the activities carried in GS2 were observed to focus more on physical intervention, which involved rule games such as Bowling, Snake and Ladder, and Bean Bag Toss games.…”
Section: Table-i: Movement Pattern Of Gs1 To Gs2 To Is B Activity Patmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as needs identified by health professionals have been reported not to capture all those identified by people with stroke [23], the individual's perspective should also be included as recommended by WHO [24]. In partnership with the healthcare professionals, the patients with stroke should be actively involved in the rehabilitation process, be able to express their needs and values, and have the opportunity to make informed decisions about their rehabilitation [21,[25][26][27][28]. Involving patients in shared decision-making has been reported to increase patient satisfaction and motivation, and create a greater sense of ownership [12,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%